A systematic review of physical activity and sedentary behavior intervention studies in youth with type 1 diabetes: study characteristics, intervention design, and efficacy. Issue 3 (29th July 2013) - MacMillan, Freya; Kirk, Alison; Mutrie, Nanette; Matthews, Lynsay; Robertson, Kenneth; Saunders, David H.
Abstract Objective To systematically review physical activity and/or sedentary behavior intervention studies for youth with type 1 diabetes. Methods Several databases were searched for articles reporting on randomized‐controlled trials (RCTs) in youth (<18 yr) with type 1 diabetes. Data was extracted and bias assessed to evaluate study characteristics, intervention design, and efficacy of interventions on physical activity and health. Where sufficient data were available meta‐analyses of health outcomes [for hemoglobin A1c (HbA1c)] were performed. Weighted mean differences (WMD) were calculated using fixed and random effect models. Results The literature search identified 12/2397 full‐text articles reporting on 11 studies. Two interventions were wholly unsupervised and only one was based on behavior change theory with no studies exploring changes in behavior processes. Nine interventions aimed to improve fitness or physical activity, two aimed to improve health, and none aimed at changing sedentary behavior. Eight interventions improved physical activity and/or fitness. At least one beneficial effect on health was found in each intervention group apart from two studies where no changes were found. Meta‐analysis of 10 studies showed the interventions have a significant beneficial reduction of HbA1c (%), indicating an improvement in glycemic control [WMD, −0.85% (95% CI, −1.45 to −0.25%)]. There were insufficient data to pool other health outcome data. Conclusions Few RCTs explored the efficacy of unsupervised theory‐based physical activity and/or sedentary behavior interventions in youth with type 1 diabetes. Limited reporting made comparison of findings challenging. There was an overall significant beneficial effect of physical activity on HbA1c.